2003
DOI: 10.1016/s0109-5641(02)00095-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficiency of plasma and halogen light sources on composite micro-hardness in different curing conditions

Abstract: Objectives. Recent developments have led to the introduction of high power curing lights, which are claimed to greatly reduce the total curing time. This study evaluated the effectiveness of a plasma-curing device (Apollo 95 E) and a halogen device (Heliolux DLX), in different curing conditions.Method. Vicker's micro-hardness values were performed on 1 and 2 mm thick composite discs cured in a natural tooth mold by direct irradiation or indirect irradiation through composite material (2 or 4 mm) and dental tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 17 publications
0
20
0
1
Order By: Relevance
“…Due to the use of different types of equipments, materials and test conditions, there is no study homogeneity among most available literature. In previous experiments; ceramic materials, artificial light filters and other analogs were applied to indirectly cure composite resin using a transmitted light beam [44,47], and then evaluated the effects on the depth of cure of composite resin. In this experiment freshly extracted human caries-free teeth were used to prepare dental slices of different thickness (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the use of different types of equipments, materials and test conditions, there is no study homogeneity among most available literature. In previous experiments; ceramic materials, artificial light filters and other analogs were applied to indirectly cure composite resin using a transmitted light beam [44,47], and then evaluated the effects on the depth of cure of composite resin. In this experiment freshly extracted human caries-free teeth were used to prepare dental slices of different thickness (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that curing through enamel is just one-third to two-thirds as effective as direct curing and is appropriate only when there is no alternative [45,46]. Another research reported the least critical record situation when 0.5mm of composite Z100 was cured through 1mm enamel [47]. Although the experiments involved through-tooth-tissue curing, only the quantitative analyses of hardness-based measurements on the degree of polymerization were employed, no qualitative analyses were done.…”
Section: Assessment Of Light-cured Composite Resin Polymerization Degreementioning
confidence: 99%
See 1 more Smart Citation
“…Yüzey sertli i yüksek dönü üm alanlar ndaki polimer çapraz ba lar n n küçük de i imlerine özellikle duyarl d r (6). Ayr ca örneklerin üst yüzeyi, orta bölgesi ve alt yüzeyi gibi örnek içerisindeki spesifik bölgelerin ölçümlerine izin verir (7). Di er bir avantaj ise sertlik de erleri ve dönü-üm derecesi aras nda, literatürde gösterilmi bir korelasyonun bulunabilmesidir (8,9).…”
Section: öZetunclassified
“…Surface hardness is an indirect measure of the degree of conversion, and important information can be obtained by comparing hardness values at the top and bottom surfaces (Dietschi, Marret & Krejci, 2003;Hofmann & others, 2002;Jandt & others, 2000;Mills & others, 1999). Many investigators have reported the top and bottom surface hardness of resin composites polymerized with different types of light curing units (Hofmann & others, 2002;Jandt & others, 2000;Leonard & others, 2002;Mc Cabe & Carrick, 1989;Mills & others, 1999).…”
Section: Introductionmentioning
confidence: 99%